Transmissão de sinais do ISDB-Tb em modulação avançada: um estudo de caso em FBMC - Almeida, Jefferson Jesus Hengles (2016)
The present work discuss the using of FBMC as modulation method for the physical layer of the Brazilian digital TV system as an alternative for OFDM. This is done in order to increase the spectral e ciency of the system, in addition to robustness and data rate. To verify hypotheses, computational implementations are used through the GNU Radio and Matlab respectively. The proper comparison between the modulations has been shown, it uses the error curves and representations in the frequency spectrum.